Implementasi Supervisi Akademik Dengan Metode 360 Derajad Untuk Meningkatkan Kemampuan Pengelolaan Pembelajaran Guru Di SD Negeri 2 Wonosari Kec. Megang Sakti Kab. Musi Rawas - Somantri , Manap; Dasim (Manajer Pendididikan, 2024)
The purpose of this study was to analyze the implementation of academic supervision with the 360 degree method to improve teachers' learning management skills at SD Negeri 2 Wonosari Kec. Megang Sakti Kab. Musi Rawas. The type of research used is school action research. The subjects of this study were 3 class teachers, namely class 1, III and V teachers. The data collection technique is observation or direct observation. The conclusions of the research are 1) The implementation of 360-degree academic supervision has a significant impact on improving teachers' lesson planning skills. This method proved effective in providing comprehensive and constructive feedback, so that teachers can identify areas that need improvement and develop better learning practices. 2) Implementing 360-degree academic supervision is the right step in improving education quality. This method has proven effective in improving teachers' skills, learning quality and the school environment. However, continuous efforts need to be made to overcome the challenges and improve the effectiveness of the supervision program. 3) The implementation of 360-degree academic supervision has shown positive results in improving teachers' learning evaluation skills. However, continuous efforts are needed to overcome the existing challenges and ensure the sustainability of this program. With support from various parties, it is expected that the quality of learning in schools can continue to improve.